Annual and monthly rainfall trend in plantation and spice farming Western Ghats districts - C K Thankamani, S J Ankegowda, K Kandiannan, K S Krishnamurthy, (Journal of Spices and Aromatic Crops, 2018)
Rainfall analysis of important plantation and spices producing districts such as The Nilgiris (Tamil Nadu), Kodagu (Karnataka) Idukki (Kerala) and Wayanad (Kerala) with 100 years data (1901 to 2000) obtained from the India Meteorological Department (IMD), Pune indicated that mean annual rainfall were 1839.7mm, 2715.7mm, 2979.4mm and 3381.0mm with a coefficient of variation (CV) of 16.0%, 17.0%, 25.8% and 19.6%, respectively. The contribution of southwest monsoon(June-September) to the annual rainfall in these districts were 80.3% (Wayanad), 78.9% (Kodagu), 65.2% (Idukki) and 56.3% (The Nilgiris) with corresponding CV of 24.1%, 20.6%, 32.5%, and 24.6%, respectively. The declining trend in mean annual rainfall was noticed for Idukki, Wayanad and The Nilgiris, whereas, for Kodagu, it was stable. The change was significant in Wayanad and The Nilgiris. Similar trend was also observed for the southwest monsoon rainfall. The maximum decline in annual and southwest monsoon rainfall was noticed in The Nilgiris followed by Wayanad. Pre and post monsoon rainfall receipts were comparatively less with high inter-annual variations. The pre-monsoon (March-May) receipt and its coefficient of variation (CV) was 252.4mm & 20.6% (Kodagu), 360.9mm & 36.5% (Idukki), 251.7mm & 36.6% (The Nilgiris) and 274.2mm & 54.2% (Wayanad). The post monsoon (October-December) rain was maximum in Idukki 548.1mm (CV 27.9%) followed by The Nilgiris 503.4mm(CV 31.3%), Wayanad, 333.1mm(CV 37.8%) and Kodagu 310.5mm (CV 32.7%). In all these districts there was a declining trend in the pre-monsoon rain with maximum decline in The Nilgiris. Similar declining trend was also observed in post-monsoon rain except for The Nilgiris, where the trend has been increasing. Overall, the study gives an indication that there was a spatial and temporal variation in rainfall amounts. The maximum decline in annual rainfall and the southwest monsoon was observed in The Nilgiris and Wayanad. July was the rainiest month in all the districts studied. Significant negative trend was asscoaited with The Nilgiris for January, May, June, July and August months. Whereas, in Kodagu, no significant trend was observed for mean monthly rainfall, except for August. In Idukki, significant negative changes were noticed for January, March, October and December rainfall. Monthly rainfall of January, March, April and July monthly rainfall were showed significant negative trend in Wayanad,. These negative trends across important plantation and spices producing districts of the Western Ghats would affect not only the agricultural economy of this sector but also water resources.